Konsep Filsafat Relasionalitas Armada Riyanto Sebagai Metode Berfilsafat di Indonesia - Mathias Adon; Charles Virgenius Setiawan; Arnold Suhardi (Pancasila: Jurnal Keindonesiaan, 2025)
This research focuses on the dialog of Armada Riyanto's concept of relational philosophy of I, Text, Other, and Phenomenon as a method of philosophizing in Indonesia. As a great nation rich in local wisdom, Indonesia needs the right philosophical method to explore the wealth of local wisdom of the tribes in the archipelago. Armada Riyanto's relationality philosophical concept of I, Text, and Other is a philosophical methodology that seeks to reach the true meaning of reality. Local wisdom is the reality of daily life in the form of tradition (ancestral heritage) which contains the philosophy, mind, and soul of the Indonesian people who appear in various forms of culture such as art, tradition, belief/ritual, and literature. This research uses a qualitative research method that dialogues Armada Riyanto's concept of philosophical relationality with the distinctiveness of Indonesian cultural concepts. This research aims to find a methodology for exploring the rich philosophical meaning of rites, symbols, ceremonies, or art in local wisdom with Armada Riyanto's philosophical method. This research found that the relational philosophy of I, Text, and Other is a philosophical methodology that can reach the true meaning of culture to prevent distortions that obscure the sense of justice in everyday life in Indonesia.